Examining how elite S&C coaches develop coaching practice using reflection stimulated by video vignettes - Szedlak, C.; Smith, M. J.; Callary, B.; Day, M. C. (International Sport Coaching Journal, 2020)
The purpose of this study was to identify narrative types that illuminate how strength and conditioning (S&C) coaches used video vignettes in a guided reflection process to support the development of effective coaching practices. At the beginning of each week, over a 4-week period, 11 elite S&C coaches were sent a short video vignette clip of an S&C coach`s practice. They subsequently engaged in daily reflections in which they were guided to explore how the topic of the vignette aligned (or not) with their coaching practice. After the intervention, each S&C coach was interviewed regarding their process of learning from the vignette and from their reflections. Using a holistic narrative analysis of form and structure, the results exemplified three narrative types: performance, achievement, and helper. The S&C coaches whose reflections fitted the performance narrative type focused on their own practice, with limited consideration of the athletes` perspective or the vignette. The S&C coaches whose reflections fitted the achievement narrative type strove to accomplish goals with their athletes and were selective in considering the vignette. The S&C coaches whose reflections fit the helper narrative type found that the vignette helped them consider an athlete-centered coaching approach focusing on the athletes` well-being, as well as athletic abilities. Thus, S&C coach developers should utilize a guided reflection process that focuses on encouraging a coaching approach based on the helper narrative type.